Is A Vending Machine My Best Bet? Understanding Key Factors Determining US Consumers’ Preference and Loyalty to Fruit Vending Machines - Botero, Julio; Rombach, Meike; Dean, David; Gan, Christopher (Jurnal Internasional Penelitian Bisnis Terapan, 2024)
This study investigates the key factors influencing US consumer preference and loyalty to fruit vending machines compared to other distribution channels. It specifically examines the roles of experience, quality and value, COVID-19, convenience, freshness, and safety-related benefits of fruit vending machines. Data was collected through an online consumer survey and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The findings reveal that the strongest predictors of consumer preference and loyalty are experience and perceived quality and value of the fruits. Convenience benefits appear significant only when comparing vending machines to other distribution channels while food safety does not emerge as a key factor. These findings add valuable insights for fruit growers and marketing managers in the US food retail sector.